Lost Mind, Lost Job? Unequal Effects of Corporate Downsizings on Employees - Petri Böckerman; Mika Haapanen; Edvard Johansson (Institute of Labor Economics (IZA), 2022)
We analyze whether employees with diagnosed mental health disorders have a higher probability of being laid off during corporate downsizing. Our analysis is based on nationwide administrative data on all private sector firms and their employees in Finland over the period 2005–2017. We focus on firms with at least 20 employees that lay off at least 20% of their total workforce between two consecutive years. We estimate whether those who have been laid off have more diagnosed mental health disorders before downsizing happens than those who have not been laid off. In our baseline specification, controlling for a rich set of employee characteristics, we find that having had any mental health disorder diagnosis in the three years that preceded the downsizing increases the probability that an employee is laid off by 6 percentage points. The results highlight that those with underlying mental health disorders are more vulnerable to losing their jobs, even in the event of a mass layoff.
Keywords: I10; I12; J64; 330; unemployment; health; mental heath; job displacement; corporate downsizing; mass layoff